Physiological and pathological tongue conditions – the role of endogenous and exogenous factors - Polina Zalewska; Małgorzata Radwan-Oczko (Medycyna Ogólna i Nauki o Zdrowiu, 2021)
Introduction and objective The tongue is considered to be a valuable source of information about patient’s general health, and it can also be an indicator of the presence or development of both local and general diseases. High frequency of occurrence and wide variety of the clinical presentations of the pathological tongue conditions result from its specific anatomical and histological structure. Multifactorial etiology of the tongue lesions and non-specificity of symptoms reported by the patients make it difficult to establish a correct medical diagnosis. The aim of the study is to present the most common tongue lesions, and to broaden knowledge of all medical specialists concerning the specific and non-specific tongue changes that can occur under the influence of local or general factors.